A 19-YEAR STORY OF ADRENAL HEMORRHAGE, ADRENAL INSUFFICIENCY, AND ADRENAL RECOVERY: DYNAMIC COSYNTROPIN RESULTS WITH TREATMENT CONSIDERATIONS - Usala, S.J. (Acta Endocrinol (Buchar), 2016)
There is limited information on the long-term natural history of adrenal function in adrenal hemorrhage following sepsis. The 19-year history of a patient is described who suffered adrenal hemorrhage during pneumococcal sepsis. Adrenal reserve using Cosyntropin testing with the 250 mcg dose was evaluated at seven time points during this interval, and a close observation of the patient enabled clinical correlation with adrenal status. The cosyntropin testing showed a 60 minute cortisol level post-hemorrhage of: 303.4 nmol/L (11.0 mcg/dL), one month; 656.6 nmol/L (23.8 mcg/dL), 1 year 10 months; and 714.5 nmol/L (25.9 mcg/dL), 19 years. Over the years the patient experienced hypoadrenal symptoms requiring both hydrocortisone and fludrocortisone until her adrenal function consistently demonstrated a 60 minute cortisol level of ~ 717.3 nmol/L (26 mcg/dL). Adrenal calcifications were visualized by ultrasound imaging and ultimately resolved. In conclusion, the patient’s hypothalamic-pituitary-adrenal system appeared to have ultimately restored normal basal adrenal function 19 years after the initial hemorrhage, and the dynamic cosyntropin data indicate that normal adrenal function should not be assumed with a 60 minute cortisol level of 496.6 – 551.8 nmol/L (18 – 20 mcg/dL). Finally, mineralocorticoid as well as glucocorticoid may be important for improved mental acuity in primary hypoadrenalism.